Effects of Advertisement on Alcohol Consumption Among Students of University of Ghana - Bremini, J. (University of Ghana, 2019)
In recent times, alcoholism has become very common among youth. The growing incidence of alcohol consumption among the youth has become a topical issue within healthcare industry because of its potential negative effects especially on student youth. To address these concerns, this study sought to identify the student youth source of information on alcohol consumption, explore their knowledge level on harmful alcohol consumption, benefits they derived from alcohol consumption and the existing national policies and their enforceability around advertising alcoholic beverages. The mixed method research design was used for the study. A total of 530 questionnaires were used to collect data from the students. Simple random and purposive sampling technique was used in selecting the students and authorities of food and drugs authority as well as advertising association of Ghana. The television set is the most watched media channel for adverts on alcoholic beverages. Majority, approximately 215 (41%) strongly agreed that, harmful alcohol consumption can cause a student to fail academic work. Closed to 299 (56%) and 172 (32%) of the participants nullified the assertion that, alcohol can enhance studies. There are existing policies and laws regulating alcoholic adverts and consumption but their enforceability is a challenge. Students have appreciable level of knowledge on alcohol consumption, its negative and positive effects. However, the absence of enforceability to regulate its consumption is a bane to controlling its intake.
Thesis (M.A.) - University of Ghana
Keywords: alcoholism; healthcare industry; advertisement; enforceability; policy; students /youth